Bandwith Optimization on Hotspot using PCQ Method And L2tp VPN Routing for Online Game Latency - Affan, Usman Ibnu; Marzuki, Khairan; Mardedi, Lalu Zazuli Azhar (International Journal of Engineering and Computer Science Applications (IJECSA), 2022)
VPN L2TP (Layer 2 Tunneling Protocol) is available on one of the services at Mikrotik. L2TP is a development of PPTP and a combination of L2F. The network security protocol and encryption used for authentication is the same as PPTP. However, to communicate, L2TP requires UDP port 1701 so that the security is better, L2TP is connected to IPSec to L2TP/IPSec. An example of its use is for the Windows operating system, which by default the Windows OS uses L2TP/IPSec. However, the consequences in terms of configuration are not as simple as PPTP. The client side must also support IPSec when implementing L2TP/IPSec. In terms of encryption, of course, encryption on L2TP/IPSec has a higher level of security than PPTP which uses MPPE. Traffic passing through the L2TP tunnel will experience overhead. The L2TP protocol is more firewall friendly than other types of VPNs such as PPTP. This is a big advantage if using this protocol, because most firewalls do not support GRE. However, L2TP does not have encryption, so it requires additional services to support higher security. So the author concludes that it will be easier to configure with online games. Online game is a type of computer game that is currently growing and requires a computer network . The networks that are usually used are internet networks or internet wifi and the like and always use current technology, such as modems and cable connections. Therefore, internet service providers (ISPs) must provide stable and fast internet quality. Bandwidth Needs Online games must be supported by an internet network that supports the speed and stability of the internet connection, especially the stability of the latency of the online game itself